2017
DOI: 10.1055/s-0037-1608668
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Absorbable and Nonabsorbable Sutures in Columellar Incision Closure in Rhinoplasty and Their Effects to Postoperative Scar

Abstract: Open technique septorhinoplasty (SRP) provides better surgical control and stronger anatomical assessment; however, one of its biggest disadvantages is postoperative columellar scar. In this study, the authos aimed to compare the absorbable polyglactin 910 (PG) (Vicryl Rapide 6/0; Ethicon Inc.) and nonabsorbable polypropylene (PP) (Prolene 6/0; Ethicon Inc.) suture materials and their effects on the postoperative columellar scar. In this study, 89 patients (61 females and 28 males) who underwent primary open t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the patients reported greater satisfaction with the use of absorbable sutures because these sutures did not require removal [ 15 ]. This aspect has been discussed in several other studies wherein researchers did not notice any difference between aesthetic outcomes with the use of absorbable or non-absorbable sutures in ear, nose, and throat or other facial surgeries [ 16 - 18 ]. Our current findings are consistent with the literature as we demonstrated that absorbable and non-absorbable sutures do not differ in terms of wound aesthetics and patient satisfaction scores.…”
Section: Discussionmentioning
confidence: 94%
“…However, the patients reported greater satisfaction with the use of absorbable sutures because these sutures did not require removal [ 15 ]. This aspect has been discussed in several other studies wherein researchers did not notice any difference between aesthetic outcomes with the use of absorbable or non-absorbable sutures in ear, nose, and throat or other facial surgeries [ 16 - 18 ]. Our current findings are consistent with the literature as we demonstrated that absorbable and non-absorbable sutures do not differ in terms of wound aesthetics and patient satisfaction scores.…”
Section: Discussionmentioning
confidence: 94%
“…Scar formation is influenced by factors such as incision and closure method, as well as postoperative care (1)(2)(3)(4). Previous studies have shown that absorbable sutures can be used safely in the columella without any long-term cosmetic concerns or an increased infection risk (5)(6)(7). Alar base reduction is usually performed during SRP when the interalar distance surpasses the intercanthal distance or when the lateral portion of the ala extends significantly beyond the alar-facial groove (8).…”
Section: Introductionmentioning
confidence: 99%